2019
DOI: 10.1039/c9ew00686a
|View full text |Cite
|
Sign up to set email alerts
|

A novel demonstration of adhered material mobilisation by hydraulic transients

Abstract: Laboratory experiments have shown that pipe-wall adhered material can be mobilised by transients, where steady-state hydraulic conditions cannot. This process is critical to managing water quality risks in drinking water distribution systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Further experiments are needed to better understand the role of daily flow variation and unsteady WSS on particle mobilization. 38…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further experiments are needed to better understand the role of daily flow variation and unsteady WSS on particle mobilization. 38…”
Section: Discussionmentioning
confidence: 99%
“…Flow acceleration has been shown to have an impact on the transport dynamics of material deposits in pipes. 38 Between flushing steps, obvert and invert pipe wall coupon samples were acquired to assess the pipe wall conditions. Bulk water samples were acquired to determine SSC during flushing.…”
Section: Experiments With Inoculation Of Iron Oxide Particlesmentioning
confidence: 99%
“…20,21 No correlation has been found between pressure and discolouration risk, 22 although hydraulic transients may contribute to material mobilisation. [23][24][25] Material accumulation, and hence discolouration risk, have been reported to be influenced by daily hydraulic conditions, 2,11,26 pipe material 15 and water temperature. 16,27 While some studies have showed temperature and microbial influence on discolouration risk, 16,[27][28][29] the variation of accumulation processes and rates seasonally has not yet been rigorously demonstrated.…”
Section: Factors Influencing Materials Accumulationmentioning
confidence: 99%
“…If transient relationships sat above the steady state relationship an area would exist where the transients can cause mobilization, but steady state cannot (green highlight). A direct implication of this research is that by reducing transient events a water utility provider could reduce the risk of discoloration contacts, the major cause of water quality related customer dissatisfaction [22]. As highlighted by Speight "Understanding the processes and interactions occurring within complex, ageing drinking water distribution systems is vital to ensuring the supply of safe drinking water.…”
Section: Potential For Pathogen Intrusion During Pressure Transientsmentioning
confidence: 99%